Impact of the Color of Rearing Tank on Behavior and Growth of Nile Tilapia, Oreochromis niloticus (Linnaeus, 1758) - Ariyomo, Tolulope Omolayo; Omobepade, Bayode Paul; Adedeji, Damilola B.; Olasunkanmi, John Bunmi; Fabusoro, Abiola Ayodeji; Jimoh, Jeremiah Olanipekun; Tope-Jegede, Oluwatosin Helen; Kelau, Shedrach Joel (Department of Aquaculture, 2024)
This study examined the impact of tank color (black, red, blue, green, and transparent) on the behavior (boldness and aggressiveness) and growth of Nile Tilapia over nine weeks (first, third, sixth, and ninth weeks). Boldness and aggression levels were assessed using open field and mirror image tests, respectively, for individual Nile Tilapia (Oreochromis niloticus). Healthy Nile Tilapia, initially weighing 2.51g on average, were used in the experimental trials conducted in tanks of different colors. The findings indicated that red tanks appeared to foster the highest level of boldness (p<0.05), whereas fish in transparent tanks exhibited the highest level of aggressiveness compared to other tanks (p<0.05). Moreover, individuals in black tanks displayed the highest growth rate in terms of weight (p<0.05). This study suggests that Oreochromis niloticus can thrive better in black-rearing tanks, as the black tanks appear to enhance the growth rate of the fish, possibly through improvements in physiological processes.